2014
DOI: 10.1038/cdd.2014.76
|View full text |Cite
|
Sign up to set email alerts
|

RIPK1 both positively and negatively regulates RIPK3 oligomerization and necroptosis

Abstract: Necroptosis is a form of programmed cell death that depends on the activation of receptor interacting protein kinase-1 (RIPK1) and RIPK3 by receptors such as tumor necrosis factor (TNF) receptor-1. Structural studies indicate that activation of RIPK3 by RIPK1 involves the formation of oligomers via interactions of the RIP homotypic interaction motif (RHIM) domains shared by both proteins; however, the molecular mechanisms by which this occurs are not fully understood. To gain insight into this process, we cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
220
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(237 citation statements)
references
References 38 publications
17
220
0
Order By: Relevance
“…It is possible that the fusion of HBD* to C-terminal of RIP3 interferes with its function. Using RIP3 with C-terminal fusion of a dimerization domain to study the effect of RIP3 dimerization on cell death was recently reported 54,55 and Orozco et al, submitted). They showed that C-terminus-mediated dimerization of RIP3D RHIM could not induce necroptosis, which is in line with our observation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the fusion of HBD* to C-terminal of RIP3 interferes with its function. Using RIP3 with C-terminal fusion of a dimerization domain to study the effect of RIP3 dimerization on cell death was recently reported 54,55 and Orozco et al, submitted). They showed that C-terminus-mediated dimerization of RIP3D RHIM could not induce necroptosis, which is in line with our observation.…”
Section: Resultsmentioning
confidence: 99%
“…This prediction is consistent with Oberst group's data that RIP1 has both positive and negative role in RIP3-mediated necroptosis. 55 As the potency of RIP3 dimer is not less than RIP3 oligomer in inducing necroptosis (Figure 4), there is not a functional requirement of forming RIP3 oligomers, although RIP3 by itself can do so in vitro. 47 If RIP3-RIP3 dimer was considered as function unit, the number of this unit, rather than whether this unit is continuously linked together (homopolyer) or randomly distributed in RIP1-RIP3 heterodimeric polymer, is important for necroptosis signaling.…”
Section: Discussionmentioning
confidence: 98%
“…In order to assess whether the suppressive effect of GW'39B was independent of the RIPK1-RIPK3 interactions, NIH-3T3 cells expressing RIPK3 ΔRHIM -2xFV were stimulated with dimerizer in the presence or absence of GW'39B (Supplementary Figure 3q). Enforced RIPK3 ΔRHIM oligomerization, which does not recruit RIPK1, 24,29 induced necroptosis, which was completely blocked by GW'39B (Supplementary Figure 3q).…”
Section: Resultsmentioning
confidence: 99%
“…Upon stimulation with TNF plus zVAD, WT MEF accumulated pMLKL over time (Figure 2d). Similarly, NIH-3T3 cells expressing exogenous dimerizable RIPK3-2xFV 24,25 displayed increased positivity for pMLKL when treated either with TNF plus zVAD (Figure 2e) or dimerizer (Figure 2f). …”
Section: Resultsmentioning
confidence: 99%
“…Under resting conditions, RIP1 is proposed to bind to RIP3 to prevent oligomerization of the latter and so prevent spontaneous RIP3 activation and necrosis. 75 This may, at least partly, underlie the perinatal lethality associated with RIP1 deficiency but would require that any such protective effects of RIP1 are independent of kinase activity as RIP1 kinase dead knockin mice survive to adulthood. 63,76,77 In addition, during development the physiological role of RIP1 in regulating RIP3-driven necroptosis appears to be highly dependent on the stage of development with RIP1 being required for TNF-induced necroptosis at E10.5 78 but inhibiting necroptosis and associated inflammation at later stages of development.…”
Section: Rip1 and Rip3 As Drivers Of Necroptosismentioning
confidence: 99%